August - Kesselring, Mari.; Collier-Morales, Roberta; Kesselring, Susan (Edina, MN : Magic Wagon, 2010)
Highlights what makes August special, including when it is, and what holidays it has.
Includes bibliographical references (p. 24).
1.0.
Pre K-2.0.
G
Accelerated Reader
Keywords: August (Month); Calendar